Dual-branch collaborative learning network for crop disease identification - Zhang, Weidong; Sun, Xuewei; Zhou, Ling; Xie, Xiwang; Zhao, Wenyi; Liang, Zheng; Zhuang, Peixian (Frontiers in Plant Science, 2023)
Crop diseases seriously affect the quality, yield, and food security of crops. Additionally, traditional manual monitoring strategies can no longer meet the efficiency and accuracy requirements of intelligent agriculture. Recently, deep learning methods have been rapidly developed in the field of computer vision. To cope with these issues, we propose a dual-branch collaborative learning network for crop disease identification, called DBCLNet. Specifically, we propose a dual-branch collaborative module using convolutional kernels of different scales to extract global and local features of images, which can effectively utilize both global and local features. Meanwhile, we embed a channel attention mechanism in each branch module to refine the global and local features. Whereafter, we cascade multiple dual-branch collaborative modules to design a feature cascade module, which further learns features at more abstract levels via the multi-layer cascade design strategy. Extensive experiments on the Plant Village dataset demonstrated the best classification performance of our DBCLNet method compared to the state-of-the-art methods for the identification of 38 categories of crop diseases. Besides, the Accuracy, Precision, Recall, and F-score of our DBCLNet for the identification of 38 categories of crop diseases are 99.89%, 99.97%, 99.67%, and 99.79%, respectively.